Modificación bioquímica del cotiledón de cacao (theobroma cacao l) en la etapa de postcosecha con la adición de levadura (Saccharomyces cerevisiae) y enzima (polifenol oxidasa) para mejorar su calidad. - Medina Velásquez, Dara Evelyn (2020)
This research aimed to improve the quality characteristics of cocoa almonds for the processing of chocolates, through the biochemical modification of cocoa cotyledon in the post-harvest stage, Thus improving the reactions within the cotyledon in almonds with the addition of yeasts (Saccharomyces cerevisiae) and enzymes (polyphenol oxidase - Pectinatransdelerase) in the post-harvest stage, performing a fermentation with yeasts and another with the addition of enzymes, in two times 3 and 4 days of fermentation, this helped to the biochemical modification within the cotyledon of cocoa almonds, improving their physical, chemical characteristics and its organoleptic attributes. The results obtained from the experimental design with the addition of yeast (Saccharomyces cerevisiae) and molasses in the post-harvest stage of cocoa have demonstrated the improvement of physical, chemical and organoleptic characteristics compared with the control. Because favorable results were obtained in T4 treatments (0,125% yeast x molasses) and T6 (0,250% molasses yeast) in terms of physical and chemical analyzes such as: Moisture, cut-off test and acidity. With regard to the experimental design of the addition of enzyme percentages (polyphenol oxidase and pectinatransdelase), it was observed in the results that there was no improvement in cocoa quality in terms of its physical and chemical analyzes such as: Test of cut, moisture, acidity, ashes and proteins, with respect to the control, but if in the case of percentage of testa, pH of testa and cotyledon. Keywords: cocoa, fermentation, enzyme, yeasts, analysis, chocolate.